Early crustal evolution of the Yangtze Craton, South China: New constraints from zircon U-Pb-Hf isotopes and geochemistry of ca. 2.9–2.6 Ga granitic rocks in the Zhongxiang Complex - Wang, Kai; Li, Zheng-Xiang; Dong, Shuwen; Cui, Jianjun; Han, Baofu; Zheng, Tao; Xu, Yilong (Precambrian research, 2018)
•Ca. 2.9–2.6 Ga granitic rocks recognized from the Zhongxiang Complex, Yangtze Craton.•Ca. 2.89–2.87 Ga, ca. 2.77 Ga, and ca. 2.67–2.62 Ga rocks show different characteristics.•The Yangtze Craton comprises multiple Archean terranes that assembled during the late Archean to Paleoproterozoic time. We report here new zircon U-Pb age and Hf-isotope as well as geochemical analyses of the recently discovered Archean-Paleoproterozoic Zhongxiang Complex in the northern-central Yangtze Craton, South China, and interpret the early crustal evolution of the Yangtze Craton. Zircon LA-ICP-MS dating yielded magmatic crystallization ages of ca. 2.90–2.87 Ga for two monzogranites, ca. 2.77 Ga for a trondhjemitic gneiss, and ca. 2.67–2.62 Ga for three potassic granites. The trondhjemitic gneiss also contains zircon rims that record a metamorphic event at ca. 2.08 Ga. These results demonstrate that the Zhongxiang Complex is significantly older than previously thought, and it contains the only potential TTG with ages of 2.8–2.7 Ga for the Yangtze Craton. These granitoids vary considerably in zircon Hf isotopic and geochemical characteristics. The ca. 2.90–2.87 Ga monzogranites correspond in composition to alkaline and calc-alkalic peraluminous granites originated from mixing of ancient and juvenile crustal components at relatively shallow depths. In contrast, the ca. 2.77 Ga trondhjemitic gneisses are calc-alkalic and peraluminous with relatively high Sr/Y and (La/Yb)N ratios and slightly evolved zircon Hf signatures, but without significant Eu anomaly that is, typical of a medium-pressure TTG component. Consequently, they are interpreted to be the products of partial melting of a basaltic source with appreciable involvement of pre-existing crustal components (i.e., tonalites), with garnet and amphibole in the residue. The ca. 2.67–2.62 Ga potassic granites are alkaline, faintly peraluminous and ferroan, exhibiting a high-silica A-type granite affinity. They are characterized by low Al2O3/TiO2 ratios with dominantly undepleted zircons, suggesting their derivation from melting of meta-sedimentary rocks under high-temperature conditions with plagioclase as the main residual phases. The Zhongxiang Complex thereby differs from the Kongling Complex and other Archean provinces in the Yangtze Craton by preserving distinct magmatic pulses (ca. 2.90–2.87 Ga; ca. 2.77 Ga; ca. 2.67–2.62 Ga) with different nature and sources. A comparative analysis of the crustal evolution of the Zhongxiang Complex and other Archean provinces of the Yangtze Craton indicates a compositionally heterogeneous Archean Yangtze Craton, which likely comprises several Archean terranes that accreted together to form a uniform craton during the late Archean to Paleoproterozoic time.